ANALISIS KELAYAKAN DAN STRATEGI PENGEMBANGAN USAHA TANI BAWANG MERAH DI KOTA PAREPARE - Satar, Muhammad; Buraerah, Sunaena (Universitas Muhammadiyah Parepare, 2020)
Onion (Allium ascalonicum L) is one of high economic value and strategic agriculture commodities, in term of the fulfillment of national consumption, raw material of bio-industry, as income source of farmer and its potency as foreign exchange income as well as for the dependence of imported onion in a particular period. The onion commodity development program is implemented by the government since 2014, so it needs a strategy in developing their farming. The research aimed to analyze the feasibility of red onion farming and formulate an alternative strategy of onion development in Parepare City. Method used in analyzing data was R/C Ratio analysis for the farming feasibility and SWOT analysis for formulating the strategy of onion development. The result of research showed that mean score of onion farming income level for each planting season was Rp. 9,633,9134.33/0.25 ha or equivalent to Rp. 38,535,563.33/ha, and R/C ratio value was 1.91. Thus, onion farming in Parepare City was efficient economically and feasible to be cultivated and developed. Furthermore, alternative strategy implemented in order to develop onion farming in Parepare City, namely: 1) improving the production and quality of product to meet market demand through illumination, training, and collaboration among farmer; 2) empowering farmer group to implement their function and role optimally; and improving the potency of farmer entrepreneurship through entrepreneurship training and comparative study or apprentice for the farmer.